2016
DOI: 10.1186/s12911-016-0390-4
|View full text |Cite
|
Sign up to set email alerts
|

Operations research for resource planning and -use in radiotherapy: a literature review

Abstract: BackgroundThe delivery of radiotherapy (RT) involves the use of rather expensive resources and multi-disciplinary staff. As the number of cancer patients receiving RT increases, timely delivery becomes increasingly difficult due to the complexities related to, among others, variable patient inflow, complex patient routing, and the joint planning of multiple resources. Operations research (OR) methods have been successfully applied to solve many logistics problems through the development of advanced analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 47 publications
0
36
0
2
Order By: Relevance
“…Thus, radiotherapy is widely used either as primary therapy, as adjuvant therapy, or as palliative treatment on the final and inoperable stages of the disease . Radiation therapy uses radioactive elements and high energy radiations produced by X‐ray equipment and particle accelerators that act directly by promoting rupture of the deoxyribonucleic acid chains, or indirectly in the production of free radicals and hydrogen peroxide resulting from the physical action of gamma irradiation in the water, leading to cellular necrosis . During radiation therapy for head and neck cancer, healthy surrounding tissues such as bones, mucosa, teeth, and salivary glands are hardly preserved …”
Section: Introductionmentioning
confidence: 99%
“…Thus, radiotherapy is widely used either as primary therapy, as adjuvant therapy, or as palliative treatment on the final and inoperable stages of the disease . Radiation therapy uses radioactive elements and high energy radiations produced by X‐ray equipment and particle accelerators that act directly by promoting rupture of the deoxyribonucleic acid chains, or indirectly in the production of free radicals and hydrogen peroxide resulting from the physical action of gamma irradiation in the water, leading to cellular necrosis . During radiation therapy for head and neck cancer, healthy surrounding tissues such as bones, mucosa, teeth, and salivary glands are hardly preserved …”
Section: Introductionmentioning
confidence: 99%
“…The image co-registration step is then followed by the contouring task, during which the various treatment volumes, i.e., the tumor, as well as the surrounding healthy tissues are contoured by a physician(s) (Vieira et al 2016). One of the axioms of radiotherapy is to maximize the prescribed radiation dose to the tumor while sparing surrounding organs at risk (Burnet 2004).…”
Section: Contouring In Radiotherapy Planningmentioning
confidence: 99%
“…The planning of radiotherapy involves a number of clinicians and tasks (Vieira et al 2016). Once radiotherapy is suggested based on the diagnosis and is discussed with the patient, the necessary data for the treatment planning, such as medical image datasets of different modalities (Batumalai et al 2016), are acquired.…”
Section: Contouring In Radiotherapy Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Operations research (OR) methods have been proposed to optimize resource planning and control in RT, as shown by Vieira et al (2016). In their review, it is shown that although most of the published studies focus on the scheduling of treatment sessions (such as Conforti et al (2010), Sauré et al (2012), and ), greater benefits in terms of waiting time reduction and resource utilization can be achieved if the pre-treatment stage is optimized jointly.…”
mentioning
confidence: 99%